Reversal of multidrug resistance by Marsdenia tenacissima and its main active ingredients polyoxypregnanes. (5th May 2017) - To, Kenneth K.W.; Wu, Xu; Yin, Chun; Chai, Stella; Yao, Sheng; Kadioglu, Onat; Efferth, Thomas; Ye, Yang; Lin, Ge
Abstract: Ethnopharmacological relevance: Multidrug resistance (MDR) of cancer is often associated with the overexpression of ATP-binding cassette (ABC) transporters, such as P-glycoprotein (P-gp), multidrug resistance-associated protein-1 (MRP-1) and breast cancer resistance protein (BCRP or ABCG2), in cancer cells, which facilitates the active efflux of a wide variety of chemotherapeutic drugs out of the cells. Marsdenia tenacissima is a traditional Chinese medicinal herb that has long been clinically used for treatment of cancers, particularly in combinational use with anticancer drugs. Polyoxypregnanes (POPs) are identified as main constituents of this herb, and three of them have been reported to exhibit P-gp modulatory effect and thus reverse MDR. Therefore, it is of great necessity to investigate more POPs that have potential to reverse transporters-mediated MDR. Aim of the study: We aimed to identify POPs as the chemical basis responsible for circumventing ABC transporters-mediated MDR by M. tenacissima . Materials and methods: The MDR reversal effects of M. tenacissima crude extract together with a series of isolated POPs were evaluated on several MDR cancer cell lines that overexpress P-gp, MRP1 or ABCG2. The activities of P-gp, MRP1 and ABCG2 were determined by the flow cytometry-based substrate efflux assay. Molecular docking of POPs to a three-dimensional human P-gp homology structure was also performed. Results: The crude extract of M. tenacissima was firstly found to circumvent P-gp-mediated MDR. Then, 11 polyoxypregnane compounds (POPs) isolated from this herb were found to overcome P-gp-, MRP1- and/or ABCG2-mediated MDR. Further mechanistic study delineated that the reversal of MDR by these POPs was due to significant increase in the intracellular concentrations of the substrate anticancer drugs via their inhibition of different ABC transporter-mediated efflux activities. Furthermore, molecular docking revealed that POPs with P-gp modulatory effect bound to P-gp and fitted well into the cavity between the alpha and beta subunit of P-gp via forming hydrogen bonds. In addition, several key structural determinants for inhibition of P-gp, MRP1 or ABCG2 by POPs were illustrated. Conclusions: Our findings advocated the rational use of M. tenacissima to enhance efficacies of conventional anticancer drugs in tumors with ABC drug transporters-mediated MDR. Furthermore, 11 POPs were found to contribute to MDR reversal effect of M. tenacissima via inhibition of different ABC efflux transporters. Graphical abstract: